(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article is about one of the important issues of identifying a person on the basis of biometric parameters, a method of distinguishing features characterizing the image. It is implemented on the basis of discrete cosine transformation of image characteristics. The study was carried out on the image of the auricle of a person.